2015
DOI: 10.33549/physiolres.933223
|View full text |Cite
|
Sign up to set email alerts
|

Different Doxorubicin Formulations Affect Plasma 4-Hydroxy-2-Nonenal and Gene Expression of Aldehyde Dehydrogenase 3A1 and Thioredoxin Reductase 2 in Rat

Abstract: Increased oxidative stress is indisputably an important mechanism of doxorubicin side effects, especially its cardiotoxicity. To prevent impairment of non-tumorous tissue and to improve the specificity in targeting the tumor tissue, new drug nanotransporters are developed. In many cases preclinical therapeutic advantage has been shown when compared with the administration of conventional drug solution. Three forms of doxorubicin -conventional (DOX), encapsulated in liposomes (lipoDOX) and in apoferritin (apoDO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another study confirmed that the higher intake of n-3 PUFA leads to a decrease in another marker of lipoperoxidation – malondialdehyde in mice tissue [ 27 ]. It should be noted that in the case of induced lipoperoxidation (e.g., doxorubicin administration [ 22 ]), the concentration of 4-HNE increases and 4-HNE is considered as a good marker reflecting the actual level of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study confirmed that the higher intake of n-3 PUFA leads to a decrease in another marker of lipoperoxidation – malondialdehyde in mice tissue [ 27 ]. It should be noted that in the case of induced lipoperoxidation (e.g., doxorubicin administration [ 22 ]), the concentration of 4-HNE increases and 4-HNE is considered as a good marker reflecting the actual level of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Various plasma oxidative stress parameters were evaluated, including determination of 4-hydroxy-2-nonenal (4-HNE), hydrogen peroxide, nitrite/nitrate ratio, total antioxidant capacity, total reactive nitrogen species, and total reactive oxygen species. The measurement of 4-HNE levels was performed by HPLC as previously described [ 22 ] by applying the reaction with 2,4-dinitrophenylhydrazine (DNPH) as derivatization reagent. The fluorometric hydrogen peroxide assay kit (MAK165, Sigma Aldrich, St. Louis, MO, USA) used to determine hydrogen peroxide.…”
Section: Methodsmentioning
confidence: 99%
“…The standard of 4-HNE was obtained from Cayman Chemical (Ann Arbor, MI, USA). Determination of 4-HNE was performed according to Kinter (1996) with slight modification as described previously (Hlaváčová et al 2015). Briefly, the 4-HNE concentration in coronary effluent was measured by HPLC with UV detection after derivatization by 2,4-dinitrophenylhydrazine and subsequently calculated according to the standard curve and expressed in nmol.min -1 .…”
Section: Biochemical Analysismentioning
confidence: 99%
“…In ischemia-reperfusion studies, numerous models including isolated heart are used due to possibility to analyze multiple parameters in detail without modulation by neurohumoral inputs (Olejníčková et al 2015). From experimentally used species, rabbit is appropriate model because of electrophysiological similarity of its heart with human myocardium (Kaese et al 2013). Predisposition of rabbit heart to spontaneous myocardial hypertrophy was previously reported (Chitty 2015).…”
Section: Introductionmentioning
confidence: 99%
“…9) Additionally, different formulations of DOX were reported to decrease TXNRD2 expression in rats. 10) Obviously, it is requisite to search for the specific effect of TXNRD2 on DOXinduced OS in cardiomyocytes.…”
mentioning
confidence: 99%